ENGAGED VERSUS DISENGAGED: THE ROLE OF OCCUPATIONAL SELF-EFFICACY - Richa Chaudhary; Santosh Rangnekar; Mukesh Kumar Barua (Asian Academy of Management Journal, 2013)
The fundamental aim of the present study among 126 business executives was to examine whether engaged workforce could be differentiated from their disengaged counterparts on the basis of occupational self efficacy, an individual difference variable. We anticipated work engagement to be characterized by high occupational self efficacy. Hence we predicted that it would correlate positively with occupational self efficacy. Fisher’s linear discriminant analysis was used to distinguish engaged employees from disengaged ones. Results showed that command and adaptability dimensions of self efficacy come out to be of most importance in distinguishing the group of engaged employees from their non-engaged counterparts. Also logistic regression analysis was carried out to see if the socio-demographic variables were contributing to the group differences. The results of the logistic regression supported the findings of discriminant analysis.